Young people and health: Towards a new conceptual framework for understanding empowerment. (January 2014) - Spencer, Grace
In recent times, empowerment has become the focus of much work with young people amidst increasing concerns about their health. Empowerment is often offered as a 'solution' to such concerns, with the uncritical assumption being made that empowerment unproblematically results in positive health outcomes. While much of the health promotion literature advocates 'empowerment', it often does so without offering a clear conceptualisation of the word itself or indeed addressing the thorny theoretical tensions surrounding the concept's root word of power . In light of this omission, this article offers a more theoretically informed conceptualisation of empowerment and considers the relationship to young people's health. This article outlines a more dynamic and generative conceptualisation of empowerment than hitherto articulated in the literature, informed by Lukes' multidimensional perspective of power. Drawing on findings from an ethnographic study on empowerment and young people's health, this article develops six conceptually distinct forms of empowerment ( impositional, dispositional, concessional, oppositional, normative and transformative ). Data were collected from 55 young men and women aged 15–16 years through group discussions, individual interviews and observational work in a school and surrounding community settings in England. Crucially, these six new forms of empowerment capture and synthesise individual, structural and ideological elements of power that differentially, and sometimes inconsistently, shape the possibilities for young people's empowerment. Of significance is the way in which these different forms of empowerment intersect to (re)produce relations of power and may offer different possibilities for health promotion.